Global Demand for Environmental Goods and Services on the Rise: Good Growth Opportunities for German Suppliers - Jürgen Blazejczak; Frauke G. Braun; Dietmar Edler (Weekly Report, 2009)
According to conservative calculations, over 580 billion was spent worldwide on environmental goods and services and renewable energy technologies1 in 2004. So-called "green spending" is set for strong growth in the future on account of the long-term expansion of the global economy and mounting environmental challenges. Significant opportunities for growth and employment in Germany are also offered by forecasted trends in the market for green technologies. DIW Berlin has developed a method to quantify future global demand for environmental goods and services based on alternative economic scenarios. The method places a key focus on the international trade of environmental goods and services. Our calculations predict that the effective annual demand for environmental goods and services in Germany will increase from 75 billion in 2004 to between 106 and 171 billion by 2020 (at 2004 prices and exchange rates).The high growth in German exports is responsible in particular for this trend. Nevertheless, sensitivity calculations indicate that demand could also grow at a much slower rate through 2020 under unfavorable economic conditions.
Keywords: Q56; Q27; F18; 330; Environmental Goods and Services Sector; World Trade; Scenarios